An Australian aged care home for people subject to homelessness: health, wellbeing and cost–benefit - Claire M. C. O’Connor; Roslyn G. Poulos; Anurag Sharma; Costanza Preti; Najwa L. Reynolds; Allison C. Rowlands; Kyall Flakelar; Angela Raguz; Peter Valpiani; Steven G. Faux; Michael Boyer; Jacqueline C. T. Close; et al. (BMC Geriatrics, 2023)
Abstract Background Older people subject to homelessness face many challenges including poor health status, geriatric syndromes, and depression, coupled with barriers in accessing health and aged care services. Many are in need of formal aged care at a younger age than the general population, yet, in Australia, specialised aged-care services to support this vulnerable cohort are limited. Methods This study was an evaluation of a new purpose-built aged care home for people with high care needs and who are homeless or at risk of homelessness. Over the first 12 months post-admission, the study examined: (1) changes in residents’ physical, mental, psychological and social health, and (2) the costs incurred by the study cohort, including any cost benefit derived. Results Thirty-five residents enrolled in the study between March 2020 – April 2021. At admission, almost half of residents were within the range for dementia, the majority were frail, at high risk for falls, and had scores indicative of depression. Over time, linear mixed-effect models showed significant improvement in personal wellbeing scores, with clinically significant improvements in overall health related quality of life. Levels of physical functional independence, frailty, and global cognition were stable, but cognitive functional ability declined over time. Comparison of 12 month pre- and post- admission cost utility data for a smaller cohort (n = 13) for whom complete data were available, suggested an average per resident saving of approximately AU$32,000, while the QALY indicators remained stable post-admission. Conclusion While this was a small study with no control group, these preliminary positive outcomes add to the growing body of evidence that supports the need for dedicated services to support older people subject to homelessness.